Analysing sources of stress among business students: Evidence from Universiti Utara Malaysia - Ong, Qi Hong (2014)
Stress could cause mental disorder to university students. It is a serious illness. A high education level with heavy burden plus unhealthy hospitality fell on students tends to create a higher student stress level. This study was carried out to determine the relationship between stressors (interpersonal, intrapersonal, academic, environment and language) and student stress. Besides, the stress level of business students and their major stress sources were identified too. A quantitative research was conducted in Universiti Utara Malaysia (UUM) with the sample size of 377 respondents. Their stress levels were measured by using the 10-items Perceived Stress Scale (PSS) while the stressors were measured by the 40-items Student Stress Survey (SSS) and 4-items Acculturative Hassles Scale for Students (AHSS). Data obtained was analyzed by using Statistical Packages for Social Science (SPSS) version 20. Results indicated student stress had the association with interpersonal sources, academic sources and environmental sources. Analysis found out 4.0% of students had low stress, 71.3% of students had moderate stress and 24.7% of students had high stress. The major student stress sources consisted of intrapersonal source‟s decline in personal health (mean = 3.97), academic source‟s increased class workload (mean = 3.75), academic source‟s lower grade than anticipated (mean = 3.71), academic source‟s anticipation of graduation (mean = 3.71) and language source‟s I am not use to the English way of thinking (mean = 3.58). In short, the stress of UUM student was significantly associated with interpersonal sources, academic sources and environmental sources. The mean value of student stress was 33.0 at moderate level. It was considerably high; hence the university management needs to develop appropriate strategy to address this issue.